Removal of agricultural wastewater pollutants by integrating two waste materials, fish scales and neem leaves, as novel potential adsorbent - Veeravalli Preetham (IWA Publishing, 2021)
Only 2.5% of the world's water is fresh, despite the fact that water covers approximately 70% of the planet. This water is used for several recreational purposes and gets polluted by wastewater disposal directly into freshwater bodies. Effluents dispersed into water bodies could be from various sources like industries, households, and agricultural activities. These effluents comprise heavy metals and chemical wastes directly released into water bodies without treatment and could include major contaminants like nitrates, nitrites, ammonia and phosphates. The present study mainly focuses on removal of four significant pollutants from agriculture wastes, i.e., nitrates, nitrites, ammonia, and phosphates. These pollutants are removed using adsorbents via a process known as adsorption. Adsorbents used in the study are fish scales and neem leaves. Several studies have been carried out to measure the efficiency of adsorbents in the removal of contaminants. These studies include equilibrium studies, kinetic studies and isotherm studies. Based on a complete analysis and results obtained, 95% to 99% of contaminants can be removed effectively with an adsorbent dosage of 0.4g (0.2 g of fish scale and 0.2 g of neem leaves powder), optimum pH of 6 and at 303K constant temperature. The dosage variance stems from changing the dosages of two adsorbents in three ways, i.e., by taking both adsorbents in equal dosages, and increasing the dosage of one adsorbent compared to the other and vice versa. The contact time varied from 0 to 140min and the Initial concentration of pollutants has also been varied from 30 to 70 mg/L. In addition to the above variations, thermodynamic studies were also done, and based on the negative values of ΔG and positive value of ΔH and ΔS, it is evident that the reaction of novel adsorbent (combination of fish scales and neem leaves) is spontaneous and endothermic. HIGHLIGHTS Agricultural wastewater pollutants causing eutrophication is one of the reasons for polluting the river bodies.; These pollutants, i.e. nitrates, nitrites, ammonia and phosphates, were treated by integrating two waste materials, fish scales and neem leaves, as single adsorbent.; About 95% to 99% of contaminants could be removed from the considered pollutant concentration.; Kinetic and isotherm studies were also included in the study.;